Survival improvement for patients with metastatic colorectal cancer over twenty years - Zeineddine, Fadl A.; Zeineddine, Mohammad A.; Yousef, Abdelrahman; Gu, Yue; Chowdhury, Saikat; Dasari, Arvind; Huey, Ryan W.; Johnson, Benny; Kee, Bryan; Lee, Michael S.; Morelli, Maria Pia; Morris, Van K.; et al. (NPJ precision oncology, 2023)
Over the past two decades of successive clinical trials in metastatic colorectal cancer (CRC), the median overall survival of both control and experimental arms has steadily improved. However, the incremental change in survival for metastatic CRC patients not treated on trial has not yet been quantified. We performed a retrospective review of 1420 patients with de novo metastatic CRC who received their primary treatment at the University of Texas M.D. Anderson Cancer Center (UTMDACC) from 2004 through 2019. Median OS was roughly stable for patients diagnosed between 2004 and 2012 (22.6 months) but since has steadily improved for those diagnosed in 2013 to 2015 (28.8 months), and 2016 to 2019 (32.4 months). Likewise, 5-year survival rate has increased from 15.7% for patients diagnosed from 2004 to 2006 to 26% for those diagnosed from 2013 to 2015. Notably, survival improved for patients with BRAF V600E mutant as well as microsatellite unstable (MSI-H) tumors. Multivariate regression analysis identified surgical resection of liver metastasis (HR = 0.26, 95% CI, 0.19–0.37), use of immunotherapy (HR = 0.44, 95% CI, 0.29–0.67) and use of third line chemotherapy (regorafenib or trifluridine/tipiracil, HR = 0.74, 95% CI, 0.58–0.95), but not year of diagnosis (HR = 0.99, 95% CI, 0.98–1), as associated with better survival, suggesting that increased use of these therapies are the drivers of the observed improvement in survival.